Secondary battery

The battery design optimizes particle sizes and layer configurations to enhance high-rate performance and prevent misalignment, ensuring efficient charge-discharge and structural integrity.

JP2025008239APending Publication Date: 2025-01-20TOYOTA BATTERY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023110224
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Secondary batteries require high-rate performance and need to suppress misalignment between layers when bent, particularly at the interface of the active material and inorganic particle layers.

Method used

The battery design includes specific particle size ratios and layer configurations, with active material particles of 2.0 μm to 15.0 μm, first inorganic particles of 0.1 μm to 1.0 μm, and second inorganic particles of 1.2 μm to 5.0 μm, ensuring a friction coefficient and electrolyte flow balance through controlled layer thicknesses.

Benefits of technology

This design enhances high-rate performance and prevents layer misalignment during bending by optimizing friction and electrolyte flow, improving both charge-discharge efficiency and structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008239000001_ABST
    Figure 2025008239000001_ABST
Patent Text Reader

Abstract

To provide a secondary battery capable of suppressing the generation of deviation between layers when bending a secondary battery while having a high rate performance.SOLUTION: A secondary battery includes: a positive electrode layer; a negative electrode layer; a separator interposed between the positive electrode layer and the negative electrode layer; and an inorganic particle layer that has a first layer interposed between the positive electrode layer and the separator and / or between the negative electrode layer and the separator, and arranged so as to be contacted to the positive electrode layer or the negative electrode layer, and a second layer contacted to the first layer and arranged to the separator side from the first layer. When a mean particle diameter of an active material 2 contained the positive electrode layer or the negative electrode layer contacted to the inorganic particle layer is A, a mean particle diameter of a first inorganic particle 4S contained in the first layer is B, and a mean particle diameter of a second inorganic particle 4L contained in the second layer is B', 10≤A / B and 1≤A / B'≤3 are satisfied.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to secondary batteries. [Background technology]

[0002] Secondary batteries are widely used in fields such as in-vehicle batteries, information and communication technology (for example, personal computers, smartphones, etc.), and power storage. For example, Patent Document 1 discloses a method for manufacturing an electrode for a nonaqueous electrolyte secondary battery, which includes a step of forming a positive electrode active material layer on a separator by spraying an active material together with a carrier gas onto the separator, and a step of forming a current collecting layer on the positive electrode active material layer by a vacuum process.

[0003] In addition, an electrode body used in a secondary battery may be provided with an active material layer containing active materials such as a positive electrode active material and a negative electrode active material, and may further be provided with an inorganic particle layer containing inorganic particles and arranged in contact with the active material layer for the purpose of improving heat resistance, etc. For example, Patent Document 2 discloses a nonaqueous electrolyte secondary battery including a positive electrode including a positive electrode active material having an olivine structure and a positive electrode current collector foil, a negative electrode including a negative electrode active material and a negative electrode current collector foil, a porous insulating layer containing inorganic fine particles interposed between the positive electrode and the negative electrode, and an ion-conductive nonaqueous electrolyte. Patent Document 3 discloses a nonaqueous electrolyte secondary battery including a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and a nonaqueous electrolyte, and further including a porous heat-resistant layer disposed between at least one of the positive electrode and the negative electrode and the separator, the porous heat-resistant layer including an inorganic filler and a binder. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-301825 A [Patent Document 2] JP 2015-232930 A [Patent Document 3] International Publication No. 2013-073011 Summary of the Invention [Problem to be solved by the invention]

[0005] Meanwhile, secondary batteries are required to have high high-rate characteristics, i.e., the ability to be charged and discharged at a high rate with a large current flowing therethrough, and from this perspective, there is a demand to improve the fluidity of the electrolyte within the secondary battery. In a secondary battery having an active material layer containing active materials such as a positive electrode active material and a negative electrode active material, and an inorganic particle layer containing inorganic particles arranged in contact with the active material layer, when the secondary battery is deformed and bent (for example, when the secondary battery is wound to form a wound battery), a shift (for example, a winding shift in a wound battery) may occur at the interface between the active material layer and the inorganic particle layer. From the viewpoint of suppressing the occurrence of such a shift between layers, it is required to increase the friction coefficient between the active material layer and the inorganic particle layer.

[0006] In view of the above circumstances, an object of one embodiment of the present disclosure is to provide a secondary battery that has high high-rate performance and can suppress the occurrence of misalignment between layers when the secondary battery is bent. [Means for solving the problem]

[0007] Means for solving the above problems include the following means. <1> A positive electrode layer; A negative electrode layer; a separator interposed between the positive electrode layer and the negative electrode layer; an inorganic particle layer interposed at least one between the positive electrode layer and the separator and between the negative electrode layer and the separator, the inorganic particle layer including a first layer arranged in contact with the positive electrode layer or the negative electrode layer, and a second layer arranged in contact with the first layer and closer to the separator than the first layer, wherein A is an average particle diameter of an active material contained in the positive electrode layer or the negative electrode layer in contact with the inorganic particle layer, The average particle size of the first inorganic particles contained in the first layer is B, When the average particle size of the second inorganic particles contained in the second layer is B', A secondary battery that satisfies the following formula 1 and the following formula 2. Formula 1 10≦A / B Formula 2 1≦A / B'≦3 <2> The average particle size A of the active material is 2.0 μm or more and 15.0 μm or less. <1> The secondary battery according to claim 1. <3> The average particle size B of the first inorganic particles is 0.1 μm or more and 1.0 μm or less. <1> or <2> The secondary battery according to claim 1. <4> The average particle size B' of the second inorganic particles is 1.2 μm or more and 5.0 μm or less. <1> ~ <3> 13. The secondary battery according to claim 12 . <5> The first layer has an average thickness of 0.1 μm or more and 1.4 μm or less, and the second layer has an average thickness of 1.2 μm or more and 7.0 μm or less. <1> ~ <4> 13. The secondary battery according to claim 12 . Effect of the Invention

[0008] According to one embodiment of the present disclosure, there is provided a secondary battery that has high high-rate performance and can suppress the occurrence of misalignment between layers when the secondary battery is bent. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of an active material layer and an inorganic particle layer used in an embodiment of the present disclosure. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating an example of a secondary battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment that is an example of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiment, and are not intended to limit the scope of the invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.

[0011] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if there are multiple substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of those multiple substances present in the composition.

[0012] <Secondary battery> A secondary battery according to an embodiment of the present disclosure includes a positive electrode layer, a negative electrode layer, a separator interposed between the positive electrode layer and the negative electrode layer, and an inorganic particle layer interposed at least one between the positive electrode layer and the separator and between the negative electrode layer and the separator. The inorganic particle layer may be disposed only between the positive electrode layer and the separator and between the negative electrode layer and the separator, or may be disposed both between the positive electrode layer and the separator and between the negative electrode layer and the separator. The inorganic particle layer includes a first layer disposed in contact with the positive electrode layer or the negative electrode layer, and a second layer disposed in contact with the first layer and closer to the separator than the first layer.

[0013] The positive electrode layer and the inorganic particle layer in contact with the positive electrode layer, and the negative electrode layer and the inorganic particle layer in contact with the negative electrode layer will be described below. Note that the positive electrode layer and the negative electrode layer will be collectively referred to as the "active material layer" below.

[0014] Here, an example of the active material layer and the inorganic particle layer used in the embodiment of the present disclosure will be described with reference to FIG. The active material layer has an active material 2, and the inorganic particle layer has small-diameter inorganic particles 4S as first inorganic particles and large-diameter inorganic particles 4L as second inorganic particles having an average particle diameter larger than that of the small-diameter inorganic particles 4S. In the inorganic particle layer, the small-diameter inorganic particles 4S form a first layer, and the large-diameter inorganic particles 4L form a second layer. In the inorganic particle layer, the small-diameter inorganic particles 4S are unevenly distributed on the active material layer side formed by the active material 2, and a part of the inorganic particles 4S is in contact with the active material 2. In the inorganic particle layer, the large-diameter inorganic particles 4L are unevenly distributed on the side opposite to the active material layer, that is, on the separator side. Note that a binder may be present in the region other than the active material 2 in the active material layer and in the region other than the small-diameter inorganic particles 4S and the large-diameter inorganic particles 4L in the inorganic particle layer, and further, an electrolyte can be present in voids formed in the binder.

[0015] Next, the relationship between the particle diameters of the active material and the inorganic particles will be described. In the present disclosure, when the average particle diameter of the active material is A, the average particle diameter of the first inorganic particles (small-diameter inorganic particles 4S in FIG. 1 ) in the first layer of the inorganic particle layer is B, and the average particle diameter of the second inorganic particles (large-diameter inorganic particles 4L in FIG. 1 ) in the second layer of the inorganic particle layer is B', Equation 1 and Equation 2 are satisfied. Formula 1 10≦A / B Formula 2 1≦A / B'≦3

[0016] For example, in FIG. 1, a first layer is formed by small-diameter inorganic particles 4S, which are the first inorganic particles, in the region of the inorganic particle layer facing the active material layer, and a second layer is formed by large-diameter inorganic particles 4L, which are the second inorganic particles, in the region of the inorganic particle layer facing the separator.

[0017] Satisfying formula 2 means that the average particle diameter B' of the second inorganic particles (large-diameter inorganic particles 4L in FIG. 1) in the second layer of the inorganic particle layer is at least 1 / 3 the average particle diameter A of the active material, indicating that the second inorganic particles are relatively large. In this way, since the second inorganic particles present in the separator-side region of the inorganic particle layer are relatively large, a flow path for the electrolyte can be secured and the fluidity of the electrolyte can be improved. As a result, the high-rate performance can be improved in the secondary battery according to the embodiment of the present disclosure. Satisfying the lower limit of formula 2 means that the average particle diameter B' of the second inorganic particles in the inorganic particle layer is 1 / 1 or less of the average particle diameter A of the active material, indicating that the second inorganic particles are not too large. If the second inorganic particles are too large, the average particle diameter A of the active material becomes relatively small, so that the flow of the electrolyte in the active material layer is relatively slower than that in the inorganic particle layer, and the balance of the fluidity of the electrolyte is deteriorated. According to the secondary battery according to the embodiment of the present disclosure, the second inorganic particles in the inorganic particle layer are not too large, and deterioration of the balance of the fluidity of the electrolyte can be suppressed, and the high-rate performance of the secondary battery can be improved.

[0018] In addition, satisfying formula 1 means that the average particle diameter B of the first inorganic particles (small-diameter inorganic particles 4S in FIG. 1) in the first layer of the inorganic particle layer is 1 / 10 or less of the average particle diameter A of the active material, indicating that the first inorganic particles are relatively small. In this way, since the first inorganic particles present in the region of the inorganic particle layer on the active material layer side are relatively small, the contact points between the active material and the first inorganic particles (contact points between the active material 2 and the small-diameter inorganic particles 4S in FIG. 1) can be increased, and the friction coefficient between the active material layer and the inorganic particle layer can be increased. Note that, if the friction coefficient between the active material layer and the inorganic particle layer is low, when the secondary battery is deformed and bent (for example, the secondary battery is wound), a slippage (for example, a slippage during winding) may occur at the interface between the active material layer and the inorganic particle layer. However, according to the secondary battery according to the embodiment of the present disclosure, since the friction coefficient between the active material layer and the inorganic particle layer is high, it is possible to suppress the occurrence of a slippage between the layers (for example, a slippage during winding) when the secondary battery is bent.

[0019] As described above, in the secondary battery according to the embodiment of the present disclosure, the particle diameters of the first inorganic particles in the first layer and the second inorganic particles in the second layer of the inorganic particle layer are adjusted to the particle diameter of the active material, thereby achieving both high fluidity of the electrolyte and high friction coefficients of the active material layer and the inorganic particle layer. As a result, the high-rate performance of the secondary battery can be improved, and the occurrence of misalignment between layers (e.g., misalignment of winding) when the secondary battery is bent can be suppressed.

[0020] (Formula 1) The ratio (A / B) of the average particle size A of the active material to the average particle size B of the first inorganic particles in the first layer is 10 or more. If the ratio (A / B) is less than 10, the coefficient of friction between the active material layer and the inorganic particle layer is not increased, and it is not possible to suppress the occurrence of misalignment between the layers when the secondary battery is bent. From the viewpoint of further increasing the coefficient of friction between the active material layer and the inorganic particle layer, the ratio (A / B) is preferably 15 or more, and more preferably 20 or more. The upper limit of the ratio (A / B) is not particularly limited, but from the viewpoint of shortening the ion diffusion path and reducing resistance, it is preferably 40 or less, and more preferably 30 or less.

[0021] (Formula 2) The upper limit of the ratio (A / B') of the average particle size A of the active material to the average particle size B' of the second inorganic particles in the second layer is 3 or less. If the ratio (A / B') exceeds 3, the fluidity of the electrolyte solution decreases, and the high-rate performance of the secondary battery cannot be improved. From the viewpoint of further increasing the fluidity of the electrolyte solution, the ratio (A / B') is preferably 2.5 or less, and more preferably 2 or less. The lower limit of the ratio (A / B) is equal to or greater than 1. If the ratio (A / B') is less than 1, the balance of the fluidity of the electrolyte is reduced, and the high-rate performance of the secondary battery cannot be improved. From the viewpoint of further improving the balance of the fluidity of the electrolyte, the ratio (A / B') is preferably equal to or greater than 1.2, and more preferably equal to or greater than 1.5.

[0022] (Average particle size A) The average particle diameter A of the active material is preferably 2.0 μm or more and 15.0 μm or less. It is preferable that it is equal to or more than the lower limit value from the viewpoint of suppressing side reactions, while it is preferable that it is equal to or less than the upper limit value from the viewpoint of increasing the specific surface area and reducing resistance. The lower limit value of the average particle diameter A of the active material is more preferably 3.0 μm or more, and even more preferably 5.0 μm or more. The upper limit value of the particle diameter A is more preferably 10.0 μm or less, and even more preferably 8.0 μm or less.

[0023] (Average particle size B) The average particle diameter B of the first inorganic particles in the first layer of the inorganic particle layer is preferably 0.1 μm or more and 1.0 μm or less. The above lower limit or more is preferable from the viewpoint of shortening the ion diffusion path and reducing the resistance, while the above upper limit or less is preferable from the viewpoint of increasing the friction coefficient between the active material layer and the inorganic particle layer. The lower limit of the average particle diameter B of the first inorganic particles is more preferably 0.2 μm or more, and even more preferably 0.4 μm or more. The upper limit of the particle diameter B is more preferably 0.8 μm or less, and even more preferably 0.5 μm or less.

[0024] (Average particle size B') The average particle diameter B' of the second inorganic particles in the second layer of the inorganic particle layer is preferably 1.2 μm or more and 5.0 μm or less. It is preferable that the average particle diameter B' is equal to or more than the above lower limit value in terms of increasing the fluidity of the electrolyte, while it is preferable that the average particle diameter B' is equal to or less than the above upper limit value in terms of increasing the fluidity of the electrolyte. The lower limit value of the average particle diameter B' of the second inorganic particles is more preferably 1.5 μm or more, and even more preferably 2.0 μm or more. The upper limit value of the particle diameter B' is more preferably 4.0 μm or less, and even more preferably 3.0 μm or less.

[0025] (Method of measuring each average particle size) The average particle diameter A of the active material, the average particle diameter B of the first inorganic particles in the first layer of the inorganic particle layer, and the average particle diameter B' of the second inorganic particles in the second layer are measured by observing a cross section of the secondary battery (a cross section parallel to the thickness direction of the active material layer and the inorganic particle layer) with a scanning electron microscope (SEM). Specifically, the average particle diameter A of the active material is determined by arbitrarily selecting 20 active material particles exposed in the cross-sectional image of the secondary battery. However, active material particles partially hidden by materials other than the active material are not selected (i.e., active material particles whose entire surface area in the cross-sectional image is exposed are selected). The area of ​​each of the 20 active material particles is determined, and the area-equivalent circle diameter (diameter of a circle with the same area) is calculated. This measurement is performed for three arbitrary cross sections, and the arithmetic average value is calculated from the obtained circle-equivalent diameters of the 60 active material particles, which is defined as the average particle diameter A of the active material.

[0026] In addition, the average particle diameter B of the first inorganic particles in the first layer is determined by arbitrarily selecting 20 first inorganic particles exposed in the first layer of the cross-sectional image of the secondary battery. However, first inorganic particles that are partially hidden by materials other than the first inorganic particles are not selected (i.e., first inorganic particles whose entire area is exposed on the surface in the cross-sectional image are selected). The area of ​​each of the 20 first inorganic particles is calculated, and the area-equivalent circle diameter (diameter of a circle with the same area) is calculated. This measurement is performed for three arbitrary cross sections, and the arithmetic average value is calculated from the obtained circle-equivalent diameters of the 60 first inorganic particles, which is defined as the average particle diameter B of the first inorganic particles in the first layer.

[0027] In addition, the average particle diameter B' of the second inorganic particles in the second layer is determined by arbitrarily selecting 20 second inorganic particles exposed in the second layer of the cross-sectional image of the secondary battery. However, second inorganic particles partially hidden by materials other than the second inorganic particles are not selected (i.e., second inorganic particles whose entire area is exposed on the surface in the cross-sectional image are selected). The area of ​​each of the 20 second inorganic particles is calculated, and the area-equivalent circle diameter (diameter of a circle with the same area) is calculated. This measurement is performed for three arbitrary cross sections, and the arithmetic average value is calculated from the obtained circle-equivalent diameters of the 60 second inorganic particles, which is defined as the average particle diameter B' of the second inorganic particles in the second layer.

[0028] The distance in the thickness direction from the interface between the inorganic particle layer and the active material layer, which is the basis for defining the first and second layers, is measured from the point where the active material and the inorganic particles contact each other. For example, in FIG. 1, the distance is measured from the point where the active material 2 and the small-diameter inorganic particle 4S contact each other. In addition, the boundary between the first layer and the second layer in the inorganic particle layer may not be clear, that is, there may be a region in which the first inorganic particles and the second inorganic particles are mixed (hereinafter referred to as a "mixed region"). In this case, the average particle size B of the first inorganic particles and the average particle size B' of the second inorganic particles are measured by selecting the first inorganic particles and the second inorganic particles, excluding the mixed region.

[0029] <Inorganic particle layer> The inorganic particle layer is a layer provided in contact with the active material layer for the purpose of improving heat resistance, etc. The inorganic particle layer includes a first layer that is disposed in contact with the active material layer and contains first inorganic particles, and a second layer that is disposed in contact with the first layer and closer to the separator than the first layer and contains second inorganic particles. In the following, both the first inorganic particles and the second inorganic particles may be simply referred to as "inorganic particles". The inorganic particle layer contains inorganic particles, and may contain, for example, a binder in addition to the inorganic particles. When the inorganic particle layer contains a binder, the inorganic particles are bound together by the binder. A large number of voids are formed between the inorganic particles at the sites not bound together by the binder, and the voids are impregnated with an electrolyte to ensure the movement of ions between the positive electrode and the negative electrode in the secondary battery.

[0030] ·Inorganic particles The material constituting the inorganic particles (first inorganic particles and second inorganic particles) is preferably an inorganic material having high electrical insulation. Examples of the inorganic material include inorganic materials (inorganic compounds) such as alumina, boehmite, magnesia, titania, silica, zirconia, zinc oxide, iron oxide, ceria, and yttria. More preferred inorganic materials include alumina, boehmite, magnesia, and titania. The inorganic materials may be used alone or in combination of two or more.

[0031] Binder Examples of the binder include acrylic resins. Examples of the acrylic resins include homopolymers obtained by polymerizing one type of monomer, such as acrylic acid, methacrylic acid, acrylamide, methacrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, methyl methacrylate, ethylhexyl acrylate, and butyl acrylate, and copolymers obtained by polymerizing two or more types of the above monomers. In addition to the acrylic resins, polyolefin resins such as styrene butadiene rubber (SBR) and polyethylene (PE), polytetrafluoroethylene (PTFE), and the like can be used. These polymers can be used alone or in combination of two or more types.

[0032] The proportion of the inorganic particles in the entire inorganic particle layer is, for example, preferably from 50% by mass to 99% by mass, and more preferably from 80% by mass to 99% by mass. When the inorganic particle layer contains a binder, the proportion of the binder in the entire inorganic particle layer is, for example, preferably from 0.5% by mass to 10% by mass, and more preferably from 0.5% by mass to 5% by mass.

[0033] Method for forming inorganic particle layer A method for forming an inorganic particle layer in a secondary battery according to an embodiment of the present disclosure will be described below, taking as an example an inorganic particle layer having the configuration shown in FIG.

[0034] As the coating liquid for the inorganic particle layer for forming the inorganic particle layer, for example, a paste-like coating liquid in which inorganic particles, a binder and a solvent are mixed and dispersed is used. First, the second layer coating liquid in which large-diameter inorganic particles 4L, which are the second inorganic particles, a binder and a solvent are mixed and dispersed is applied to the surface of the separator and dried to form the second layer. Next, the first layer coating liquid in which small-diameter inorganic particles 4S, which are the first inorganic particles, a binder and a solvent are mixed and dispersed is applied to the surface of the second layer and dried to form the first layer. This makes it possible to form an inorganic particle layer having the configuration shown in FIG. 1, in which the second layer of large-diameter inorganic particles 4L, which are the second inorganic particles, and the first layer of small-diameter inorganic particles 4S, which are the first inorganic particles, exist. It is also possible to form the inorganic particle layer by applying a first layer coating liquid to the active material layer, drying the first layer coating liquid, and then applying a second layer coating liquid to the active material layer, and drying the second layer coating liquid.

[0035] The solvent used in the coating solution for the inorganic particle layer may be water or a mixed solvent mainly composed of water. As the solvent other than water constituting such a mixed solvent, one or more organic solvents (lower alcohols, lower ketones, etc.) that can be mixed uniformly with water may be appropriately selected and used. Alternatively, organic solvents such as N-methylpyrrolidone (NMP), pyrrolidone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, toluene, dimethylformamide, dimethylacetamide, etc., or a combination of two or more of these may be used.

[0036] -Average thickness of the first and second layers of the inorganic particle layer From the viewpoint of making it easier to increase the coefficient of friction between the active material layer and the inorganic particle layer, the average thickness of the first layer in the inorganic particle layer is preferably 0.1 μm or more and 1.4 μm or less, more preferably 0.3 μm or more and 1.2 μm or less, and even more preferably 0.5 μm or more and 1.0 μm or less. From the viewpoint of easily increasing the fluidity of the electrolyte, the average thickness of the second layer in the inorganic particle layer is preferably 1.2 μm or more and 5.0 μm or less, more preferably 1.8 μm or more and 4.4 μm or less, and even more preferably 2.4 μm or more and 3.8 μm or less.

[0037] The average thicknesses of the first layer and the second layer in the inorganic particle layer are determined by arbitrarily measuring the thicknesses of 10 locations for each of the first layer and the second layer in the cross-sectional image of the secondary battery, and taking the arithmetic mean value as the average thickness. Note that in the inorganic particle layer, the boundary between the first layer and the second layer may not be clear, that is, there may be a region (mixed region) where the first inorganic particles and the second inorganic particles are mixed. In this case, the thickness of the first layer refers to the distance from the interface between the first layer and the active material layer to the middle position in the thickness direction in the mixed region. Also, the thickness of the second layer refers to the distance from the interface on the separator side in the second layer to the middle position in the thickness direction in the mixed region.

[0038] <active material layer> The active material layer contains an active material and can contain, for example, a binder in addition to the active material. The active material layer includes a positive electrode layer and a negative electrode layer.

[0039] The positive electrode layer contains, for example, a positive electrode active material and a positive electrode binder. The positive electrode active material is, for example, a material capable of occluding and releasing lithium ions. Examples of the positive electrode active material include lithium nickel-based oxides, lithium cobalt-based oxides (e.g., LiCoO2, etc.), and lithium manganese-based oxides (e.g., LiMn2O4). Examples of the lithium nickel-based oxides include LiCoO2, ternary lithium transition metal oxides, and solid solution-type lithium-excess transition metal oxides. The ternary lithium transition metal oxide is represented by the general formula (A): Li(Li a Mn x Co y Ni z )O2 (where a, x, y, z in formula (A) satisfy a + x + y + z ≒ 1 and xyz ≠ 0). The solid solution-type lithium-excess transition metal oxide is represented by the general formula (B): xLi[Li 1 / 3 Mn 2 / 3 O2·(1 - x)LiMeO2 (where Me is one or more transition metals in formula (B) and x satisfies 0 < x ≦ 1). Examples of the positive electrode binder include fluororesins (for example, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, etc.), polyvinyl acetate, and the like. The positive electrode layer may contain, as necessary, a conductive assistant (for example, acetylene black, etc.), a thickener, a surfactant, a dispersant, a wetting agent, an antifoaming agent, etc.

[0040] The negative electrode layer contains, for example, a negative electrode active material and a negative electrode binder. The negative electrode active material is, for example, a material capable of absorbing and releasing lithium ions (for example, a carbon material (for example, natural graphite, artificial graphite, etc.)). Examples of the negative electrode binder include fluororesins (for example, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, etc.), polyvinyl acetate, and the like. The negative electrode layer may contain, as necessary, a conductive assistant (for example, acetylene black, etc.), a thickener, a surfactant, a dispersant, a wetting agent, an antifoaming agent, etc.

[0041] <Structure of secondary battery> Next, an example of a secondary battery according to an embodiment of the present disclosure will be described with reference to Fig. 2. The secondary battery 100 has a positive electrode including a positive electrode current collector 32 (e.g., aluminum foil, etc.) and a positive electrode layer 34 including a positive electrode active material formed on both sides of the positive electrode current collector 32. The secondary battery 100 also has a negative electrode including a negative electrode current collector 22 (e.g., made of copper) and a negative electrode layer 24 including a negative electrode active material formed on both sides of the negative electrode current collector 22. The secondary battery 100 has a structure in which the positive electrode and the negative electrode are laminated with a separator 60 interposed therebetween. The secondary battery 100 is configured to include predetermined battery constituent materials (active materials for the positive and negative electrodes, current collectors for the positive and negative electrodes, a separator, etc.) similar to a typical lithium secondary battery.

[0042] The secondary battery 100 further has an inorganic particle layer 62 between the negative electrode layer 24 and the separator 60. In the embodiment shown in FIG. 2, the inorganic particle layer 62 is formed on one surface of the separator 60 facing the negative electrode layer 24.

[0043] The positive electrode current collector is a metal foil (for example, aluminum foil, etc.). The negative electrode current collector may be, for example, copper foil.

[0044] The separator may be, for example, a porous resin flat plate, and the material of the resin flat plate may be resin (for example, polyethylene, polypropylene, etc.).

[0045] The electrolyte used in the secondary battery is preferably, for example, a non-aqueous electrolyte. The non-aqueous electrolyte contains an electrolyte and a non-aqueous solvent. The electrolyte may be a lithium salt containing fluorine (e.g., lithium hexafluorophosphate, lithium tetrafluoroborate, etc.), or a lithium salt not containing fluorine (e.g., lithium perchlorate, lithium tetrachloroaluminate, etc.). The non-aqueous solvent may be a cyclic carbonate (e.g., ethylene carbonate, etc.), or a chain carbonate (e.g., dimethyl carbonate, ethyl methyl carbonate, etc.). The non-aqueous electrolyte may further contain an additive (e.g., lithium bis(oxalato)borate, etc.). EXAMPLES

[0046] Examples will be described below, but the present invention is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.

[0047] Example 1 A secondary battery having the configuration shown in FIG. 2, in which the negative electrode layer (active material layer) and the inorganic particle layer have the configurations shown in FIG. 1, was fabricated.

[0048] Formation of inorganic particle layer First, the second layer coating liquid, which is a mixture of inorganic particles (material: boehmite) having an average particle size shown in "second inorganic particles B'" in Table 1 as the second inorganic particles, a binder (material: acetamide-based polymer) and a solvent (water), was applied to the surface of the separator and dried to form the second layer. Next, the first layer coating liquid, which is a mixture of inorganic particles (material: boehmite) having an average particle size shown in "first inorganic particles B" in Table 1 as the first inorganic particles, a binder (material: acetamide-based polymer) and a solvent (water) was applied to the surface of the second layer and dried to form the first layer. This formed an inorganic particle layer. The average thickness of the formed first layer was 0.8 μm, and the average thickness of the formed second layer was 3.7 μm.

[0049] In addition, a positive electrode current collector (aluminum foil), a positive electrode layer including a positive electrode active material (material: lithium transition metal oxide), a negative electrode current collector (copper foil), a negative electrode layer including a negative electrode active material (material: graphite), and a separator were formed by a known method. However, as the negative electrode active material, an active material having an average particle size shown in "Active Material A" in Table 1 was used. In this way, a secondary battery having a configuration in which an inorganic particle layer including the first layer and the second layer is interposed between the negative electrode layer and the separator was obtained.

[0050] (Examples 2 to 3) A secondary battery was obtained in the same manner as in Example 1, except that inorganic particles having an average particle diameter shown in "Second inorganic particles B'" in Table 1 were used as the second inorganic particles, inorganic particles having an average particle diameter shown in "First inorganic particles B" in Table 1 were used as the first inorganic particles, and an active material having an average particle diameter shown in "Active material A" in Table 1 was used as the negative electrode active material.

[0051] (Comparative Examples 1 to 4) The formation of the inorganic particle layer was changed to the following method. A coating solution for the inorganic particle layer, which was prepared by mixing and dispersing inorganic particles (material: same as in Example 1) having the average particle diameters shown in "First inorganic particle B" and "Second inorganic particle B'" in Table 1 as inorganic particles, a binder (material: same as in Example 1), and a solvent (same as in Example 1), was applied to the surface of the separator and dried to form an inorganic particle layer. A secondary battery was obtained in the same manner as in Example 1, except that the formation of the inorganic particle layer was changed to the above method. The average thickness of the formed inorganic particle layer was 4.5 μm.

[0052] (Comparative Examples 5 to 7) A secondary battery was obtained in the same manner as in Example 1, except that inorganic particles having an average particle diameter shown in "Second inorganic particles B'" in Table 1 were used as the second inorganic particles, inorganic particles having an average particle diameter shown in "First region inorganic particles B" in Table 1 were used as the first inorganic particles, and an active material having an average particle diameter shown in "Active material A" in Table 1 was used as the negative electrode active material.

[0053] -Average particle size- The average particle size A of the active material, the average particle size B of the first inorganic particles in the inorganic particle layer, and the average particle size B' of the second inorganic particles in the inorganic particle layer were measured by the above-mentioned methods. The results are shown in Table 1.

[0054] -Evaluation test: Winding slippage (friction coefficient)- As an index of misalignment, the "friction coefficient (static friction coefficient)" between the active material layer (negative electrode layer) and the inorganic particle layer was measured by the following method. The electrode plate and the separator were used to measure the static friction coefficient according to JIS K7125:1999. Specifically, a separator with an inorganic particle layer formed thereon similar to that in each Example and Comparative Example, and an anode layer (electrode plate) including an anode current collector and an anode active material similar to that in each Example and Comparative Example were prepared. The anode layer (electrode plate) was placed so that the active material layer was in contact with the inorganic particle layer in the separator, and the electrode plate was slid over the separator at a speed of 100 mm / min to measure the static friction coefficient. In addition, a measured friction coefficient of 0.45 or more was judged as "A (pass)," and a measured friction coefficient of less than 0.45 was judged as "B (fail)." In Table 1, those rated as B (fail) are underlined.

[0055] -Evaluation test: High rate (resistance increase rate)- As an index of high-rate characteristics, the resistance increase rate was measured by the following method. The secondary batteries obtained in each Example and Comparative Example were charged and discharged 400 times at a high rate of 30 C, and the internal resistance [mΩ] of the battery was measured before and after each charge and discharge. The internal resistance [mΩ] of the battery after charge and discharge was calculated as an index, where the internal resistance [mΩ] of the battery before charge and discharge was set to 1, and this index was used as an index of the resistance increase rate. In addition, a resistance increase rate (i.e., the calculated index) of less than 1.18 was judged as "A (pass)," and a resistance increase rate of 1.18 or more was judged as "B (fail)." In Table 1, the samples rated as B (fail) are underlined.

[0056] [Table 1]

[0057] As shown in Table 1, the secondary batteries of the Examples, in which the value of A / B satisfied formula 1 and the value of A / B' satisfied formula 2, had a higher friction coefficient of the inorganic particle layer than those of Comparative Examples 2, 4, and 5, in which the value of A / B did not satisfy formula 1. Furthermore, the secondary batteries of the Examples showed higher high-rate performance than those of Comparative Examples 1, 3, 6, and 7, in which the value of A / B' did not satisfy formula 2. [Explanation of symbols]

[0058] 2 Active material 4S Small diameter inorganic particles 4L Large inorganic particles 22 Negative electrode current collector 24 Negative electrode layer 32 Secondary battery 34 Positive electrode layer 60 Separator 62 Inorganic particle layer 100 Secondary battery

Claims

1. A positive electrode layer; A negative electrode layer; a separator interposed between the positive electrode layer and the negative electrode layer; an inorganic particle layer interposed between the positive electrode layer and the separator or between the negative electrode layer and the separator, the inorganic particle layer including a first layer disposed in contact with the positive electrode layer or the negative electrode layer, and a second layer disposed in contact with the first layer and closer to the separator than the first layer; an average particle size of the active material contained in the positive electrode layer or the negative electrode layer in contact with the inorganic particle layer is designated as A; The average particle size of the first inorganic particles contained in the first layer is B, When the average particle size of the second inorganic particles contained in the second layer is B′, A secondary battery that satisfies the following formula 1 and the following formula 2. Formula 1 10≦A / B Formula 2 1≦A / B'≦3

2. The secondary battery according to claim 1 , wherein the average particle diameter A of the active material is 2.0 μm or more and 15.0 μm or less.

3. The secondary battery according to claim 1 , wherein an average particle diameter B of the first inorganic particles is 0.1 μm or more and 1.0 μm or less.

4. The secondary battery according to claim 1 , wherein the second inorganic particles have an average particle size B′ of 1.2 μm or more and 5.0 μm or less.

5. 2. The secondary battery according to claim 1, wherein the first layer has an average thickness of 0.1 μm or more and 1.4 μm or less, and the second layer has an average thickness of 1.2 μm or more and 7.0 μm or less.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and electrode used for the same, and method of manufacturing them

    JP2009301825A

  • Nonaqueous electrolyte secondary battery

    JP2015232930A

  • Non-aqueous electrolyte type secondary battery

    WO2013073011A1